PENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY, REPETITION (AIR) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN XI MIA SMAN 8 PEKANBARU - Winda Sihotang; Maria Erna; Erviyenni Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
bstract: This study aims to determine the improve of student achievement by implemented of Auditory, Intellectually, Repetition (AIR) on solubility equlibrium subject at class XI MIA SMAN 8 Pekanbaru. The type of research was an experiment with randomized control group pretest-posttest design. The sample in this research is class XI MIA 7 as experiment class and class XI MIA 8 as control class which is determined randomly after normality test and homogenity test. The experimental class was treated with the implementation of Auditory, Intellectually, Repetition (AIR) while the control class without the implementation of Auditory, Intellectually, Repetition (AIR). Data analysis for hypothesis testing is done using right-t test. Based on the results of data analysis obtained tcount = 3,254 with = 0,05, dk =69 and obtained that tcount > ttable is 3,254 > 1,67 means the implementation of Auditory, Intellectually, Repetition (AIR) learning model can improve student’s learning achievement on solubility equlibrium subject at class XI MIA SMAN 8 PekanbaruKeywords: Auditory, Intellectually, Repetition (AIR), Learning achievement, solubility equlibrium